A route selection algorithm for WiMAX mobile multi-hop relay networks - Satiman, N. (IEEE Explorer, 2011)
Next generation of wireless broadband network such as WiMAX MMR networks and LTE Advanced support high quality multimedia services with high data transmission rate. Most of the current broadband operates at high frequency and thus has limited transmission range. Multi-hop relaying technology is seen as an efficient solution that could enhance coverage and improves system capacity. However, overall system performances worsen as the number of hop increases. Providing efficient route selection is one of the key issues to be tackled to improve overall system performance in multi-hop relay network. In this paper, we propose route selection algorithm based on channel condition for WiMAX Mobile multi-hop relay network. We conducted simulation study to evaluate the performance of the proposed scheme.